Tax Avoidance in Indonesian Banking: The Role of Transfer Pricing and Corporate Ownership - Qashash Medya Supriyanto; Bima Cinintya Pratama; Eko Hariyanto; Ani Kusbandiyah (Journal of Finance and Business Digital, 2022)
This research was conducted to examine the factors affecting tax avoidance, including transfer pricing, institutional ownership, and foreign ownership. This research also examines the role of institutional ownership and foreign ownership as moderating variables. The samples of this study was conventional banks registered with the Financial Services Authority with a sample of 41 conventional banks during the 2017 – 2021 period. In testing the hypothesis of this study using panel data regression analysis. The analysis techniques used in this study were descriptive statistical tests, preliminary tests (Breusch-Pagan, likelihood tests, Hausman tests), diagnostic tests (heteroscedasticity tests and autocorrelation tests), and hypothesis testing. Based on the results of the three preliminary tests in determining the panel data regression model, this study will use the fixed effect model to examine the relationship between variables in regression models 1 and 2. This study reveals that transfer pricing has a negative effect on tax avoidance, the smaller the receivables owned by the company the smaller the company will do tax avoidance.